Measuring violence against children: The adequacy of the International Society for the Prevention of Child Abuse and Neglect (ISPCAN) child abuse screening tool - Child version in 9 Balkan countries. (October 2020) - Meinck, Franziska; Murray, Aja L.; Dunne, Michael P.; Schmidt, Peter; ,; Nikolaidis, George; Petroulaki, Kiki; Zarokosta, Foteini; Tsirigoti, Antonia; Hazizaj, Altin; Cenko, Enila; Brikc-Smigoc, Jelena; et al.
Abstract: Objective: Violence against children is a global public health concern. Researchers are increasingly using self-report measures of physical, psychological, and sexual violence and neglect for population-based surveys. The current gold-standard measure, the 45-item ISPCAN Child Abuse Screening Tool has been used across the world. This study assesses its adequacy for measuring abuse across countries. Methods: Multiple group confirmatory factor analyses were used to assess the configural, metric and scalar invariance of the measure across nine Balkan countries. Data were collected using a three-stage stratified random sampling frame of 42, 194 school-attending children in three grades (aged 11, 13 and 16 years) from schools in Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, North Macedonia, Romania, Serbia, and Turkey. Children completed the ICAST-C, which measures children's exposure to physical, psychological, and sexual violence, neglect and witnessing household violence in the past year and across the lifespan. Results: The analyses show partial scalar invariance for the ICAST-C constructs children's exposure to physical and psychological violence, neglect and witnessing household violence across the nine countries and partial scalar invariance for the constructs of children's exposure to physical, psychological and sexual violence, neglect and witnessing household violence across eight countries (Turkey did not measure sexual violence). Conclusions: The ICAST-C can be used to validly compare levels of physical, psychological, and sexual violence, neglect and witnessing violence in school-aged children across countries. It can also be used to validly compare the relations between these forms of violence and their covariates, predictors, and outcomes across countries.